Food Service Delivery, Hygiene Practice and Passengers Satisfaction at Transport Terminal: a case of Akure, Ondo, Nigeria - Odesanya, Joseph; Oyetoro, H. K. (Journal of Science, Technology and Innovation Research, 2026)
Food safety remains a pressing global public health concern, with the informal food sector playing a critical role in providing accessible meals, particularly in transit hubs such as motor parks. This study examines passengers’ assessments of service quality and hygiene standards among food vendors in Akure’s motor parks, aiming to evaluate safety in food delivery. Using a quantitative survey approach, data were gathered via structured, closed-ended questionnaires from 167 randomly selected passengers. Results indicate that service delivery was generally satisfactory, with tangibility receiving the highest mean score (3.6048), followed by reliability, assurance, and responsiveness. However, empathy received the lowest score (3.3832), highlighting the need for improved attention to individual customer needs. In contrast, hygiene practices were perceived less favorably. Although many respondents agreed on some aspects of hygiene, the average mean score of 3.2827 and a mode of 4 reflect widespread dissatisfaction. Statistical analyses further supported this finding: a strong positive correlation (R = 0.753, p = 0.000) was observed between perceived hygiene practices and reported incidents of food borne illness. This suggests that poor hygiene practices are significantly associated with higher reports of food borne diseases among passengers. Regression analysis confirmed the model’s robustness (F = 301.336, p = 0.000), with an R² of 78.6%, indicating that passenger perceptions of hygiene and service delivery strongly predict overall satisfaction. The study recommends that government and relevant agencies prioritize public and vendor education on hygiene.